2019
DOI: 10.1016/j.bandl.2019.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Continuous theta burst stimulation over right pars triangularis facilitates naming abilities in chronic post-stroke aphasia by enhancing phonological access

Abstract: Background: Repetitive transcranial magnetic stimulation (rTMS) has been used experimentally to facilitate naming abilities in individuals with chronic post-stroke aphasia. However, little is known about how rTMS confers clinical improvement, hampering its therapeutic value. The present study investigated the characteristics of naming failure that improve following administration of continuous theta burst stimulation (cTBS)-an inhibitory form of rTMS-to the right pars triangularis (rPTr) in persons with chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…Manipulating of synaptic transmission by rTMS is suggested to be based on the long‐term potentiation or depression‐like phenomena of synaptic plasticity. Most prior studies of low‐frequency rTMS (mostly 1 Hz) over right Broca's homologue area in aphasia patients showed benefits in picture naming . To the best of our knowledge, this would be the first case report showing the physiological effect of cTBS over Broca's homologue area on the reorganization of language network in aphasia patient, which was similar to 1 Hz stimulation.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Manipulating of synaptic transmission by rTMS is suggested to be based on the long‐term potentiation or depression‐like phenomena of synaptic plasticity. Most prior studies of low‐frequency rTMS (mostly 1 Hz) over right Broca's homologue area in aphasia patients showed benefits in picture naming . To the best of our knowledge, this would be the first case report showing the physiological effect of cTBS over Broca's homologue area on the reorganization of language network in aphasia patient, which was similar to 1 Hz stimulation.…”
Section: Discussionsupporting
confidence: 54%
“…Most prior studies of low-frequency rTMS (mostly 1 Hz) over right Broca's homologue area in aphasia patients showed benefits in picture naming. 1,2,[5][6][7] To the best of our knowledge, this would be the first case report showing the physiological effect of cTBS over Broca's homologue area on the reorganization of language network in aphasia patient, which was similar to 1 Hz stimulation. There was one study that observed cTBS effect on behavioral outcome by measuring the response time of picture naming in normal subjects, which was shorter after cTBS.…”
Section: Discussionmentioning
confidence: 53%
“…More generally, extended data from aphasic discourse in languages like Greek are expected to contribute to the investigation of its linguistic properties in comparison with other languages; for example, the pilot version of GREAC has been compared to English and Hungarian data, suggesting that word frequency distribution is similar to non-aphasic discourse, whereas differences between languages can be related to languages' morphological properties and particular language impairments (Neophytou et al, 2017). The detailed error annotation can also provide important evidence for the distribution of error types, especially the pervasive phonological vs. semantic distinction (Schuchard et al, 2017;McKinnon et al, 2018;Harvey et al, 2019), as well as of sub-categories of error types, that is the relative frequency of substitution, omission, addition etc. in order to test the findings of earlier linguistic studies of aphasic discourse (e.g., Blumstein, 1973;Lesser, 1995).…”
Section: Circumlocutionsmentioning
confidence: 99%
“…The detailed error annotation can also provide important evidence for the distribution of error types, especially the pervasive phonological vs. semantic distinction (Schuchard et al, 2017 ; McKinnon et al, 2018 ; Harvey et al, 2019 ), as well as of sub-categories of error types, that is the relative frequency of substitution, omission, addition etc. in order to test the findings of earlier linguistic studies of aphasic discourse (e.g., Blumstein, 1973 ; Lesser, 1995 ).…”
Section: Contribution Of the Corpusmentioning
confidence: 99%
“…[ 11 ] This approach is significant for patients with abnormal brain tissue because it allows contralateral stimulation of the normal brain to improve connectivity through this mechanism of downregulating contralateral excitement. [ 9 , 11 , 21 ]…”
Section: Introductionmentioning
confidence: 99%